Energy management schemes for distributed energy resources connected to power grid - Srishail K Bilgundi; Heerayan Pradeepa; Aditi Kadam; Likithkumar M. Venkatesh (Institute of Advanced Engineering and Science, 2022)
In a technically advanced world where demand is increasing very fast especially large number of non-linear loads and electric vehicles has led to energy crisis and pollution of grid power. Depleting conventional energy sources and environmental concerns has led to integration of large number of distributed energy resources (DERs) at distributional level to resolve problem of energy crisis and reduce emissions. With grid connected to different types of DERs, it is very challenging to manage the power flow, resolve energy crisis and maintain good power quality. Improper energy management may lead to inefficient operation of DERs and may build up stress on energy storage systems (ESS) impacting their life cycle. Thus, it is necessary to use energy management schemes (EMS) for efficient and reliable operation. EMS helps to enhance overall system efficiency and reduce the stress on ESS. This paper presents the analysis of different EMS applied on distribution system for efficient and economic operation of DERs and carryout stress analysis on ESS. Overall system efficiency, Hydrogen utilization in fuel cell, state of charge (SoC) of batteries and supercapacitor are the main parameters considered for performance comparison. To analyze the proposed work a simulation model is designed in MATLAB.